1882 N.M. Laws 313 - (:unkn) unknown (My University, 1882)
Ch. 61, Deadly Weapons. Act of 1869, Ch. 32, § 4: Any person who shall draw a deadly weapon on another, or who shall handle a deadly weapon in a threatening manner at or towards another, in any part of this Territory, except in the lawful defense of himself, his family, or his property, or by order of legal authority, upon conviction thereof before the proper tribunal, shall, for each offense, be fined in a sum not less than twenty-five dollars nor more than seventy-five dollars, or by imprisonment in the county jail for a term of not less than twenty days or more than sixty days, or be punished by both such fine and imprisonment, in the discretion of the jury trying the case. § 5. Any person who shall draw or use any deadly weapon in any ball, dance, or other public gathering of the people, or near where any election authorized by law is being held in any part of the Territory, except it be in the lawful defense of himself, his family, or his property, or in obedience to legal authority, shall, upon conviction before the proper tribunal, be punished by a fine not less than fifty dollars nor more than one hundred dollars for each offense, or by imprisonment in the county jail for a term of not less than one month nor more than three months for each offense, or by both such fine and imprisonment, in the discretion of the jury trying the cause.
Keywords: BRANDISHING; GOING ARMED